2012
DOI: 10.1111/j.1750-3841.2012.02657.x
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of a Database of Food Ingredient Fraud and Economically Motivated Adulteration from 1980 to 2010

Abstract: Food ingredient fraud and economically motivated adulteration are emerging risks, but a comprehensive compilation of information about known problematic ingredients and detection methods does not currently exist. The objectives of this research were to collect such information from publicly available articles in scholarly journals and general media, organize into a database, and review and analyze the data to identify trends. The results summarized are a database that will be published in the US Pharmacopeial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
351
0
21

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 670 publications
(374 citation statements)
references
References 18 publications
2
351
0
21
Order By: Relevance
“…The economic value of olive oils make this food product very prone to fraud, including mislabeling of olive oil commercial category, geographical or olive cultivar origin [3][4][5][6][7]. So, several gas-, liquid-and mass-spectrometry chromatography, DNA and spectroscopy based methods have been developed to assess olive oil quality and authenticity as well as to detect possible adulterations [3,5,6,[8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The economic value of olive oils make this food product very prone to fraud, including mislabeling of olive oil commercial category, geographical or olive cultivar origin [3][4][5][6][7]. So, several gas-, liquid-and mass-spectrometry chromatography, DNA and spectroscopy based methods have been developed to assess olive oil quality and authenticity as well as to detect possible adulterations [3,5,6,[8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…By definition, adulteration is a food product modification that results in a change of the identity and/or purity of the original ingredients, performed by substituting, diluting, or modifying them by physical or chemical means [6]. As an example, food can be adulterated by the introduction of an inert material or even of dangerous substances as such a practice can lead to an increase of the economic profits of the producer [45].…”
Section: Food Frauds Under the Spotlightmentioning
confidence: 99%
“…In the last 15 years, fraudulent events have occurred regularly, generating economic, ethical, safety, and socioreligious effects [45,46]. In this regard, Moore et al described in their paper a comprehensive compilation of information about food fraud ingredients into a database [6]. The authors analyzed scholarly journals, media, and other reports to obtain useful information to develop the database.…”
Section: Food Frauds Under the Spotlightmentioning
confidence: 99%
“…Adulteration in milk with other dairy or non-dairy ingredients has become very common [1,2]. In fact, milk is one of the seven top foods that is adulterated at all levels of the production process, and this fact has been widely recorded [3]. Recently, in Brazil was reported that commercial ultra-high temperature milks available in the Brazilian market presented at least one adulterant, such as starch, chlorine, formaldehyde, hydrogen peroxide and urine [4].…”
Section: Introductionmentioning
confidence: 99%